An experimental and numerical study of flow distribution chambers - Wong, Voon Hon (Cranfield University, 1999)
Flow distribution chambers are devices commonly used by the water industry to distribute flows in water and sewage treatment plants. These have simple designs, and are required to operate over a range of volumetric flowrates. Many chambers surveyed (Herbath and Wong, 1997b) were found to perform poorly. They suffered from flow mal-distribution, where the flow was not distributed according to design. The most common cause of flow mal-distribution was hypothesised to be due to the presence of a pipe bend below the chamber (Herbath and Wong, 1997a, 1997b). Therefore, an experimental and numerical study of the flow within a distribution chamber was conducted in this thesis to prove this hypothesis. A novel large-scale model (1: 13) of a typical distribution chamber was constructed. This allowed the collection of high quality and novel velocity and turbulence measurements near the free surface using hot film anemometry. The free surface location was measured using a vernier point gauge while the flow distribution between the outlets was metered by orifice plates. Records of the flow patterns were also kept. The experimental results showed that flow mal-distribution did not occur as expected since the model distribution chamber was designed with a long length of straight inlet pipe, to eliminate the suspected cause of flow mal-distribution. Novel velocity and water surface data were also collected in the experiments, which contributed towards the small body of knowledge in this area of research into flow distribution. CFD models of the physical model were created and solved using a commercial CFD code, CFX 4.1, developed by CFX International of AEA Technology. Steady state and transient two- and three-dimensional calculations of the symmetrical chamber were carried out in the course of the study. A novel adaptation of the existing code was made in obtaining solutions to the numerical models. A new solution strategy was made and refined in this stage of the research using the two-dimensional representation of the distribution chamber, for reasons of reduced computational time. Differencing schemes, surface sharpening, mass residuals, mesh refinement and different turbulence models were investigated during model refinement. The accuracies of the calculated results were determined by comparison with experimental results. It was found that the 3D model, incorporating the RNG k-c model, without surface sharpening, and using the Van Leer differencing scheme, gave good quantitative agreement with the experimental velocities, free surface location and flow distribution. The 2D results gave qualitatively good predictions. Quantitatively, the results were over-predicted which was due, to dimensional effects. The volume of the 2D model was reduced from the 3D model, while the inlet velocity was made the same. This replicated the momentum effects near the free surface that were the governing causes of flow mal-distribution. Nevertheless, this approach was much more practical in terms of computational effort. More importantly, the correct trends for flow mal-distribution could be predicted accurately. Therefore, the next stage of the research used the 2D model developed and validated here. This part of the research involved the novel adaptation of the existing symmetrical 2D results for investigating the asymmetric effects of pipe bends. Three different approaches for modelling the asymmetric effects of a pipe bend were investigated. The first, and the most simplistic, was to incline the incoming flow at an angle to the vertical. The second was to calculate the velocities and turbulence at the outlet of a simple 2D pipe bend, separate from the chamber. These calculated variables were then input into the chamber, to build up a picture of the asymmetric flow, iteratively. The third, and the most accurate method, was to couple the bend to the chamber. It was found that only the third method was capable of accurately representing the conditions within the chamber. Two different pipe bend. lengths were examined using the third approach. The distances chosen were typical of the bend distances found in some treatment plants. The results . from both simulations produced large flow mal-distribution and asymmetric flows within the chamber. A value of 10% difference between the flows from the two outlets was taken to be the maximum limit for mal-distribution. However, values of 44.5 % and 22.8 % were obtained for the larger pipe distance and short pipe distance respectively. Novel remediation strategies using numerical techniques were used to determine the most effective means of improving the flow distribution. The first, used a vertical flow splitter, placed directly above the chamber inlet. Although it altered the path of the jet, it was felt that it would be ineffective for all situations. Although the magnitude of the asymmetry was improved with the use of the splitter, the improvement was insufficient to warrant its recommendation. The other device tested was a horizontal plate located at a certain distance from the chamber inlet. For the longer bend case, a separation distance equivalent to two inlet hydraulic diameters was sufficient to deflect the jet, and reduced the magnitude of the flow asymmetry to around 2%. When the same plate location was used for the shorter bend case, the efficiency of the plate was reduced. Although there was an improvement in the distribution, the magnitude of the asymmetry was greater than 10%. The plate was subsequently lowered by half a hydraulic diameter. This gave a large improvement to the effectiveness of the plate, and the resulting asymmetry was reduced to 7.31 %. The horizontal plate was considered more promising since its function was to deflect and reduce the peak velocities of the jet. With the reduction in velocities, the magnitudes of the nonlinear terms in the Navier-Stokes equations are reduced. The solution to the equations would be more likely to be symmetrical.